Сказки в картинках - Сутеев Владимир Григорьевич (Библиотека начальной школы, 2015)
Экземпляры: ф.7 (20161006) / Инвентарный номер: 41720 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 90 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6